Factors Affecting Nursing Students' Knowledge of Sports Injury Management - Tasnim, Marwan; Fitriana, Lisna Anisa; Rohaedi, Slamet; Sumartini, Sri; Irawan, Erna; Maidartati, M; Iklima, Nurul (SAFE-Network, 2024)
Knowledge about handling sports injuries is crucial for nursing students at Universitas Pendidikan Indonesia (UPI), who actively participate in various sports activities. This study analyzes the factors influencing students' knowledge in managing injuries. The influencing factors are categorized into internal factors—such as education, experience, age, and interest—and external factors, including mass media, socio-cultural influences, economic conditions, and environmental aspects. A cross-sectional research design was employed, involving 84 nursing students from UPI. Data were collected using a 90-item questionnaire, and analysis was conducted using the t-test. The results indicate that internal and external factors significantly influence students' knowledge of handling sports injuries, with a significance level of less than 0.05 (p < 0.05). This suggests that improvements in the internal and external factors correlated with enhanced knowledge among nursing students regarding sports injury management. These findings underscore the importance of enhancing both internal and external factors to improve nursing students' capabilities in sports injury management. Conversely, a decline in these factors corresponds with diminished knowledge levels. It is recommended that further research include a larger sample size to strengthen these findings.